Table of Content - - (Journal of medical and pharmaceutical sciences, 2025)
Table of Content: 1. Evaluation of the Quality of Health Services at Turkish Palestinian Friendship Hospital in Gaza Strip, Palestine: Patients’ Perspective Dr. Eman Suliman Hassouna 2. The Role of Mobile Health (mHealth) in Enhancing Healthcare Delivery in Remote Areas: A Systematic Review Muhammad Obaid M. Alotaibi